The educational effects of telemedicine training using role‐playing for general practice/family medicine residents: A qualitative study - Koki Nakamura; Tomoo Hidaka; Yoshihiro Toyoda; Mei Endo; Satoshi Kanke (Journal of General and Family Medicine, 2025)
Abstract Background Despite the increasing demand for telemedicine, there have been few reports on telemedicine training for general practice/family medicine residents. This study aimed to qualitatively examine the educational effects of remote medical training for residents using role‐play. Methods This study targeted first‐ and second‐year residents enrolled in the General Medicine/Family Medicine Residency Program at Fukushima Medical University in 2023. The residents watched educational videos on telemedicine and engaged in role‐playing training based on multiple scenarios. Subsequently, interviews were conducted with the residents, and the verbatim transcripts of the audio data were thematically analyzed using open coding. Results Eight residents participated in the study, with each undergoing 3–4 interviews. The identified codes were inductively summarized, and nine categories were generated: verbal cues to enhance the quality of history taking, nonverbal communication to connect with patients, addressing risks inherent in the convenience of telemedicine, co‐creating a clinical environment with patients, anticipating issues different from those encountered in face‐to‐face consultation rooms, considering and supporting the elderly and those who are digitally disadvantaged, improving access restrictions due to busyness and resistance to telemedicine, understanding the living environment in connection with patient families and home care nurses, and awareness of the wide‐ranging applications of telemedicine. Conclusion The results of telemedicine training via role‐play suggest various educational effects. This study provides crucial findings for considering educational methods for GM/FM residents to respond to the increasing demand for telemedicine in primary health care.